Evaluation of the effectiveness of the Iran-package of essential non-communicable disease (IraPEN) program in reducing cardiovascular disease risk in pilot areas - Somayeh Derakhshan; Davood Khalili; Alireza Mahdavi; Seyed-Saeed Hashemi-Nazari; Amir Kavousi; Fatemeh Hadavandsiri; Afshin Ostovar; Koorosh Etemad (BMC Public Health)
Abstract Background To assess the effectiveness of the IraPEN program in decreasing the risk of cardiovascular disease (CVD) and associated risk factors in selected areas of Iran. Methods A secondary data analysis of longitudinal data collected between 2016 and 2017 from health centers in four pilot areas. The target population consisted of people aged 40 years and above, as well as individuals aged 30–40 years who had at least one CVD risk factor. We compared mean CVD risk and risk factor levels before and one year after the intervention and utilized Generalized Estimating Equations to analyze the trends during subsequent visits. Results A total of 160,223 eligible individuals (93,081 female) were screened at baseline, of which 25,764 individuals (17,386 female) were followed up for at least one year. The proportion of men with a CVD risk score above 10%, according to the WHO/ISH risk charts, decreased from 7.5 to 5.3%, while the proportion of women decreased from 6.1 to 4.7%. Based on the revised WHO risk score, the mean CVD risk for those with a risk score above 10% at baseline and one year later was 0.198 and 0.177 in men and 0.119 and 0.109 in women, respectively. There was a significant decrease in all risk factors, except for waist circumference in both sexes and BMI in women. The trend analysis of risk factors over time confirmed these findings. Conclusion The program was modestly effective in reducing CVD risk in the pilot areas. However, further modifications may be needed to enhance its effectiveness.